On the Decay and Global Existence of Solutions to a Nonlinearly Damped Wave Equation with Variable Exponents and Delay - Kafini, Mohammad; Al-Mahdi, Adel M.; Al-Gharabli, Mohammad M. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we consider a nonlinear wave equation with variable exponents and time-varying delay. We prove a global existence result using the well depth method and by a lemma by Komornik, we establish the decay estimates for the solution under suitable assumptions on the variable exponents m,p and the initial data. This work generalizes and extends several works in the literature.